Participação institucionalizada e resistência popular na intervenção em favelas: o caso Vila Antena - Tamiris Joana do Nascimento (2011)
This work analyzes the conflict between prefecture technicians and residents of Vila Antena, in Belo Horizonte, during the Vila Viva slums intervention program's execution. This research's criticism approaches two aspects of this conflict: first, the land ownership problem, apparent reason for the residents' resistance with the public defendants against Belo Horizonte's prefecture and its associated management and executive agencies. Secondly, and the main focus of this research, I investigate how the participative structure proposed in the PGE's elaboration prevents actual popular participation, as well as any kind of dialogue, information exchange and local empowerment; essentially functioning as a means of pacification and public municipal policy propaganda. This research's methodology is based on bibliographic revision about the aforementioned topics, including historical aspects and, mainly, field research. The field research is made on the second semester of 2009, during which I follow and attend to the meetings between the Vila Antena residents and the Public Defense, prefecture and other agents involved in the process; besides interviewing communitary leaderships and gathering reports and data from the residents. In the work's conclusion, I highlight possibilities for urban insurgencies based on information mediation and popular instrumentalization as alternatives to institutionalized participation- acknowledging the limitations inherent to this proposition, under an autonomist perspective and the need for discussion and continuous action.